Deconvolution in Intravascular Ultrasound to Improve Lateral Resolution. (July 2019) - Li, Mingxia; Shao, Weiwei; Jiang, Xiaoning; Feng, Zhihua
Intravascular ultrasound (IVUS) is an important diagnostic method for coronary disease. The lateral and axial resolutions of IVUS systems under study are typically ~120 and ~30 µm, respectively. The lateral resolution has a lower quality than the axial one and is restricted by the aperture size of transducers. In addition, this resolution is difficult to further improve physically. However, IVUS is inherently suitable for lateral deconvolution because of its circular imaging area. In this paper, magnitude-based deconvolution was demonstrated to be feasible in IVUS imaging to improve the lateral resolution. The deconvolution process was first simulated to determine the highest feasible resolution. Next, the method was applied to a real system to validate the feasibility. The lateral resolution was improved significantly, that is, 2°-separated targets could be discerned using a transducer with 4.2° –6 dB lateral resolution.